Synthesis by Different Methods and Characterization of Hyperbranched Polyurethane - Chen, Guangmei; Liu, Chao; Hu, Dongfeng (Asian Journal of Chemistry, 2013)
Hyperbranched polyurethane (HBPU) samples are synthesized by two different methods from isophorone diisocyanate, 1,4-dihydroxybutane and diethanolamine generation by generation. And two series of samples are marked HBPU1s and HBPU2s. FTIR measurement is used to characterize the structure of the samples. DSC and TG measure the thermal properties of the samples. The results indicate that the hyperbranched structure of the polyurethane is consistent with theoretical design through controlling the feed ratio. The intensity of hydrogen-bonded interaction in HBPU1s is stronger than that in HBPU2s. Two series samples have same thermal stability.